Adhesive Strength of Glass Fiber-Reinforced Posts with Silane Conditioning Versus Universal Adhesive System Conditioning: An In Vitro Study - Martínez-Campos, Reynaldo (2024)
Aim: The current study compared the push-out adhesive strength of glass fiber-reinforced posts with a silane-treated surface versus a universally adhesive-treated surface. In both cases, a universal self-adhesive cement was used. Materials and Methods: Thirty bovine teeth were used in an in vitro experiment. Through cutting, the root and coronal sections were divided. Subsequently, the manufacturer’s recommendations were followed for the placement of glass fiber-reinforced posts through root canal therapy, gutta-percha removal, and canal shaping. On the basis of how the posts were treated prior to cementation, the samples were split into three groups (n = 10). Posts in group A (control) did not get any prior treatment. Posts in group B had previously received a silane treatment. Posts in Group C had previously been coated with universal adhesive. Following the application of RelyX Ultimate universal self-adhesive cementation, the samples were segmented and subjected to a Push-Out test at a speed of 1 mm/min on a universal testing apparatus. Intergroup ANOVA was used to evaluate the adhesive strength means (measured in MPa), and Tukey’s post hoc test was performed afterward, with a significance level of P < 0.05. Results: Compared to the glass fiber-reinforced posts pre-treated with silane (P = 0.003) and the control group (P < 0.001), the adhesive strength of the posts pre-treated with universal adhesive was significantly higher. Similarly, the adhesive strength of the glass fiber-reinforced posts that had been pre-treated with silane was considerably higher than that of the control group (P = 0.012). Conclusion: Posts reinforced with glass fiber and pre-treated with universal adhesive exhibited notably greater adhesive strength compared to those pre-treated with silane. When compared to utilizing universal self-adhesive cement without pre-treatment, both pre-treatment techniques greatly increased the adhesive strength of glass fiber-reinforced posts.